"Cornella" (Cookies Bekatul Jagung dan Rosella) Sebagai Snack Alternatif Pencegah Diabetes Mellitus - Puspita, Siska Jufia; Wahyuni, Eka; Antasari, Roro; Tri C, Suhaeli; Wijaya, Faradyta (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
World health organization (who) in 2010 reported 60 % cause of death all age in the world is because ptm and diabetes mellitus ranked 6th as cause of death, One of the factors dm the most high derived from a diet that is wrong. Corn bran a corn grinder waste that is considered less useful but many of its nutrition value such as energy content of 356 kilokalori, protein 9 g, carbohydrates 64.5 grams, calcium 200 mg, 10 mg, iron, vitamin A as much as 0 IU, etc. Rosella is a diabetes drug crops is still underutilized by society, Hence we mengemasnya in the cookies the easy consumed and healthy.Pkm-k aims that âcornellaâ be food an alternative for diabetics mellitus and can prevent DM, âcornella â is a business opportunity which promises because raw materials widely available, still not be used in an inefficient manner and the absence of a snack products are beneficial to health especially prevent dm, Cornellaâ have a look and a unique flavour with a relatively inexpensive price Rp. 20.000/pack..Marketing using brochures and cooperate with the cakes and the surrounding community, get profit Rp 989.800. Next, hopefully accepted by company pastries, producing in a larger scale and employs workers in manufacturingÂ Keywords : Cornella, Diabetes Mellitus, corn barn, rosella